2019
DOI: 10.1002/prot.25761
|View full text |Cite
|
Sign up to set email alerts
|

Structural effects of divalent calcium cations on the α7 nicotinic acetylcholine receptor: A molecular dynamics simulation study

Abstract: The α7 subtype of neuronal nicotinic acetylcholine receptor (nAChR) is a ligand-gated ion channel protein that is vital to various neurological functions, including modulation of neurotransmitter release. A relatively high concentration of extracellular Ca 2+ in the neuronal environment is likely to exert substantial structural and functional influence on nAChRs, which may affect their interactions with agonists and antagonists. In this work, we employed atomistic molecular dynamics (MD) simulations to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Although the conformational changes due to calcium binding are likely smaller than those due to agonist binding (Li et al, 2011), these smaller changes may prime the receptor so that changes elicited by agonist are either more stable or occur more rapidly. A recent study in which MD simulations were applied to a model of the full-length α7 nAChR also revealed conformational changes in the presence of calcium that were consistent with a partially activated state (Suresh and Hung, 2019).…”
Section: Natarajan Et Almentioning
confidence: 84%
“…Although the conformational changes due to calcium binding are likely smaller than those due to agonist binding (Li et al, 2011), these smaller changes may prime the receptor so that changes elicited by agonist are either more stable or occur more rapidly. A recent study in which MD simulations were applied to a model of the full-length α7 nAChR also revealed conformational changes in the presence of calcium that were consistent with a partially activated state (Suresh and Hung, 2019).…”
Section: Natarajan Et Almentioning
confidence: 84%
“…Blockage of α9 and α9α10 nAChRs occurs in the millimolar range, is voltage-dependent, and proposed to occur as a result of Ca 2+ permeation [18,47]. On the other hand, potentiation of α9α10 receptors is voltage-independent [18], suggesting that, similar to that proposed for α7 receptors [17,21,[48][49][50], Ca 2+ most likely interacts at an extracellular binding site to allosterically modulate coupling between ligand-binding and gating [18].…”
Section: Introductionmentioning
confidence: 98%
“…In this regard, extracellular calcium (Ca 2+ ) has been reported to increase macroscopic currents and change the kinetic properties of several native and recombinant nAChRs and has been classi ed as an allosteric modulator of these receptors [13][14][15][16][17][18][19]. Moreover, previous studies revealed that Ca 2+ binding leads to similar but smaller conformational changes than those due to agonist binding, that are consistent with a partially activated state [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, computational modeling and simulation offer the ability to study protein at the atomistic level, albeit at the expense of some accuracy. 23,24 One such computational approach is molecular dynamics (MD) simulations that can provide atomistic details of the protein structure and dynamics and validate experimental observations. 25,26 However, atomistic MD simulations can be very computationally expensive, especially if large-scale conformational changes are being studied.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Despite the success of experimental techniques to determine the structural features of proteins, the experimental study of dynamic transitions between conformations remains extremely challenging. On the other hand, computational modeling and simulation offer the ability to study protein at the atomistic level, albeit at the expense of some accuracy. , One such computational approach is molecular dynamics (MD) simulations that can provide atomistic details of the protein structure and dynamics and validate experimental observations. , However, atomistic MD simulations can be very computationally expensive, especially if large-scale conformational changes are being studied. Such simulations are typically able to capture dynamics at the nanosecond to microsecond (ns to μs) timescales. , To increase these timescales, coarse-grained (CG) MD models can be used. , In CG models, a mapping scheme is used to represent a group of atoms as beads, leading to a reduction in the degrees of freedom and hence longer simulation timescales.…”
Section: Introductionmentioning
confidence: 99%